مدى تمكين مراكز التطوير وضمان الجودة في الجامعات اليمنية من ممارسة مهامها من وجهة نظر قياداتها - البناء, خالد داحش علي (Journal of Amran University, 2021)
The research problem is summarized in the roles that the development and quality assurance centers must be applied in Yemeni Universities, where it is relied upon to reach Universities to the ranks of advanced educational institutions. These centers are the base that raises the level of universities in form and content and deepens the principles of strength, capacity and efficiency of the product, which is the student scientifically and practically. Paying attention to these centers in advanced universities has become one of their top priorities. Became lead the Universities to Advanced Quality Levels, the research is Self Evaluation which aims at achieving the following: Knowing The Extent of Empowerment of Academic Development Centers and assure the Quality in Yemeni University by practicing the different roles. Knowing the affection of this centers in achieving their Goals and Message. Conclude the Technical & Administrative Difficulties which face these Centers. The researcher showed the Previous Studies which talk about the Total Quality in University Institutions and Obstacles and Difficulties which face those Institutions. The results obtained in those studies were reviewed in order to benefit from them in determining the roles that the academic development and quality assurance centers should play in order to advance the Yemeni Universities and bring them to their advanced levels.